UJI PRAKTIKALITAS ALAT PERAGA BANDUL MATEMATIS BERBASIS MIKROKONTROLLER SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - Putra, Angga Suhardi; M. Rahmad, M. Rahmad; Sudrajat, Hendar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the practicality level of mathematical pendulum experimental device based on microcontroller. This device consists of tools and mathematical pendulum device test based on microcontroller students worksheet which are used as medium of physics learning in senior high school. This research used research and development method. Respondents of this research are 3 high school teachers and 20 students of class X science of SMAN 8 Pekanbaru and MAN 1 Pekanbaru. Data collection techniques are done by giving a practicality questionnaire to teachers and students. The data were analyzed descriptively to determine the value of the practicality of experimental device. Descriptive analysis showed that the practicality of mathematical pendulum props based on microcontroller was in very high category with average score 3,90 and 3,40. Likewise, the assessment on the practicality of students’ works sheet is rated very high by teachers and students with average score 3.67 and 3.42. Therefore, mathematical pendulum experimental device based on Microcontroller and Students’ worksheet is declared practical to be used as a physics learning media in senior high school.Key Word : Mathematical pendulum props based on microcontroller, Students’ worksheet, Practicality, Physics learning Media